2016
DOI: 10.3390/ijerph13050467
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Groundwater Contaminant Transport at a Decommissioned Landfill Site—A Case Study, Tainan City, Taiwan

Abstract: Contaminant transport in subsurface water is the major pathway for contamination spread from contaminated sites to groundwater supplies, to remediate a contaminated site. The aim of this paper was to set up the groundwater contaminant transport model for the Wang-Tien landfill site, in southwestern Taiwan, which exhibits high contamination of soil and groundwater and therefore represents a potential threat for the adjacent Hsu-Hsian Creek. Groundwater Modeling System software, which is the most sophisticated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…The GMS software is a comprehensive package, which is widely used to model groundwater flow in the world [35,36]. The procedure for applying to a groundwater flow model includes four steps: (1) in-situ information collection; (2) conceptual model construction; (3) simulation and calibration of groundwater flow model; (4) predictive simulation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GMS software is a comprehensive package, which is widely used to model groundwater flow in the world [35,36]. The procedure for applying to a groundwater flow model includes four steps: (1) in-situ information collection; (2) conceptual model construction; (3) simulation and calibration of groundwater flow model; (4) predictive simulation.…”
Section: Methodsmentioning
confidence: 99%
“…For a long time (several decades), human activity has been the main influencing factor of groundwater storage. According to the statistical development report on paddy fields and annual official report on water resources, the paddy field acreage was enlarged more than 25 times over the last three decades, and in addition to that, 10 times more groundwater was pumped [26,36,38].…”
Section: Factors Influecing the Groundwater Storage Changementioning
confidence: 99%
See 1 more Smart Citation
“…The anthropogenic sources are generally ascribed to extreme use of agricultural, pesticides and fertilizers, mining wastes, disposal of industrial wastes, waste disposal sites, and imperfect well construction [22]. Chen et al (2016) [23] simulated the groundwater contamination in Tainan City, Taiwan, and the study revealed that the total mass of pollutants in the aquifer increased by 72% after 10 years. [24] studied the groundwater quality of Turfy Swamps in the Changbai Mountain area below the highway as the related pollutant, and showed a great influence on the groundwater quality of these wetlands with increasing highway operation time.…”
Section: Introductionmentioning
confidence: 99%
“…The migration of these substances in water surface and rock ambient poses a major threat to the environment, especially to the quality of surface and groundwater [ 1 ]. There are studies dealing with the modelling of the migration of these substances in groundwater in Taiwan [ 2 ], along with efforts to influence the quality of leachate directly in situ using adsorbent materials based on zeolite and perlite [ 3 ]. Taking into account that landfilling is, and in the near future will continue to be, one of the most widespread methods of waste disposal, it is necessary to study this issue in detail.…”
Section: Introductionmentioning
confidence: 99%